2017
DOI: 10.18632/oncotarget.14871
|View full text |Cite|
|
Sign up to set email alerts
|

Silence of cancer susceptibility candidate 9 inhibits gastric cancer and reverses chemoresistance

Abstract: Cancer Susceptibility Candidate 9 (CASC9) is a novel gene generating long non-coding RNA (lncRNA) with oncogenic potential that was first identified in esophageal cancer. In this study, we have found that CASC9 was overexpressed in gastric cancer (GC) compared to normal gastric tissue. A higher expression level was associated with aggressive pathological characteristics, including deep invasion, poor differentiation and lymph node metastases. In two gastric cancer cell lines, BGC823 and SGC7901, CASC9 were bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 14 publications
6
39
0
Order By: Relevance
“…For further in‐depth analysis, the lncRNA CASC9 , whose knockdown by three different methods was consistently associated with a loss of cell viability, was selected. The link of CASC9 to viability and proliferation was further supported by data from other tumor entities . We showed that the impact of CASC9 depletion was caused by a mixed phenotype including loss of proliferation and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For further in‐depth analysis, the lncRNA CASC9 , whose knockdown by three different methods was consistently associated with a loss of cell viability, was selected. The link of CASC9 to viability and proliferation was further supported by data from other tumor entities . We showed that the impact of CASC9 depletion was caused by a mixed phenotype including loss of proliferation and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…We showed that the impact of CASC9 depletion was caused by a mixed phenotype including loss of proliferation and induction of apoptosis. Other studies linked the cellular phenotype of CASC9 to impaired epithelial–mesenchymal transition (EMT) and invasion . However, previously suggested CASC9 target genes involved in EMT, like vimentin, cadherins 1 and 2, and SNAIL family transcriptional repressor 1, were not differentially expressed, which might indicate tumor type–specific differences.…”
Section: Discussionmentioning
confidence: 97%
“…18 Recently, researchers reported that CASC9 could be a predictor of poor prognosis in ESCC. 22,23 Our results confirmed the high expression level of CASC9 in ESCC tumor tissues, and trans-analysis inferred the potential regulatory correlation of CASC9 with MYZAP, a myocardial-related gene. 20,21 CASC9 also plays an oncogene in many other malignancies such as gastric cancer and nasopharyngeal cancer.…”
Section: Discussionsupporting
confidence: 75%
“…The patient characteristics are shown in Supplemental Table 1 (supplemental material available online with this article; https://doi.org/10.1172/JCI96218DS1). As shown in Figure 1A, the microarray analysis identified 158 upregulated and 142 downregulated lncRNAs from 7,419 analyzed lncRNAs in the MIBC tissues, including CASC9, MIAT, MEG3, and LINC01133, which are associated with human cancer progression (25)(26)(27)(28). Additionally, one lncRNA (LINC00958, RefSeq accession number NR_038904), Figure 1.…”
Section: Blacat2 Overexpression Correlates With Ln Metastasis Of Bladmentioning
confidence: 99%